مستوى الـ PSA والمرحلة السريرية لسرطان الموثة والجراحة الجذرية - ياسين قصاب, إسلام (Latakia University Journal -Medical Sciences Series, 2019)
تناول البحث / 29 / مريضاً لديهم سرطان بروستات تمت معالجتهم ومتابعتهم في قسم الجراحة في مشفى الأسد الجامعي باللاذقية خلال القترة ما بين 1999-2003 . تبين أن نسبة الحدوث العظمى في العقد السابع من العمر بنسبة 48,27 %, وكانت الصورة السريرية الأكثر مشاهدة هي الأعراض الإنسدادية السفلية المترافقة بالآلام العظمية بنسبة 34,48 % ونسبة زيادة الـPSA بين 100-139 نغ / مل شوهدت عند 44.82 % من المرضى, وأكثر المراحل السريرية مشاهدة عند التشخيص كانت المرحلة CT3b بنسبة 65,51 وبالتالي كان العلاج الهرموني هو الأكثر استخداماً بسبب تأخر التشخيص حيث أجري بنسبة 93,1% وكان ذو نتائج غير مرضية وكانت نسبة معدل الحياة خمس سنوات بعد هذا العلاج 37.93% . بينما أجري العلاج الجراحي الجذري بنسبة 6,89 % وكانت ذاو نتائج ممتازة. هذا ما يدعونا للتأكيد الشديد على الفحص الدوري والمتضمن (المس الشرجي – عيارة الـ PSA) سنويا بعد سن الخمسين للكشف المبكر عن السرطان وتقديم الحل الأفضل وهو الحل الجراحي. 29 patients having prostatic cancer were treated and observed at al-Assad Hospital in the period between 1999-2003. It has shown that the highest rate of incidence during the seventh decade is 48.27%. The most observed clinical symptoms were the lower obstructive disterbences and the bone pains at the rate of 34.48%. The PSA rate between 100-139 ng/ml was observed in 44.82% of patients. The observed clinical stages at dignosis were cT3b at the rate of 65.51%, so the hormonic treatment is mostly used due to delay of dignosis, which was given to 93.1% of cases, and the results were unsatisfactory because the survival rate in the five-year period was 37.93%. The radical surgical treatment was applied to 6.89% of patients and gave excelent results. As a result, we insist on periodic tests (digital rectal examination, PSA titer) yearly after the age of fifty for early detection of prostatic cancer in order to give the best solution, which is the radical surgical solution.